2017
DOI: 10.5797/jnet.tn.2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique of Safe and Versatile Microguidewire Shaping with Neuroendovascular Therapy: Modified Pigtail Method

Abstract: Objective: A tip shape of a microguidewire that is safe and highly versatile in coil embolization of cerebral aneurysms was evaluated.Case Presentations: Case 1: A 65-year-old woman with subarachnoid hemorrhage due to rupture of an anterior communicating artery aneurysm which was coil-embolized 7 years before. The aneurysm recanalized and regrew thereafter, and an additional embolization was performed. Angiography before treatment showed 50% stenosis at the origin of the right internal carotid artery (ICA). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…In a previous study, it was reported the usefulness of pigtail shaped of microguidewire as a method to safely guide a microguidewire into a perforator or occluded vessel that is not visible on angiography. 14) This method enables the assessment of thrombus rigidity based on intraoperative changes in the microguidewire shape and may be reflected by thrombectomy procedures. 15) If a CCF develops during endovascular treatment in patients with AIS, as demonstrated in the present case, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, it was reported the usefulness of pigtail shaped of microguidewire as a method to safely guide a microguidewire into a perforator or occluded vessel that is not visible on angiography. 14) This method enables the assessment of thrombus rigidity based on intraoperative changes in the microguidewire shape and may be reflected by thrombectomy procedures. 15) If a CCF develops during endovascular treatment in patients with AIS, as demonstrated in the present case, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used an MGW with a modified pigtail shape to achieve this spiral pattern. [ 6 7 ] The results obtained show that the beanstalk method may be effective for decreasing the ledge effect. The gap between the catheter and the MGW traveling along the exterior of a tortuous vessel decreased in size with the use of this novel technique, compared with the use of a parallel double MGW.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have previously reported that the use of an MPMGW is an extremely safe and versatile method for neuroendovascular procedures. [2][3][4][5][6] The round tip of the wire prevents unintentional entry into the perforating branches or blebs of an aneurysm and reduces the risks of perforation if it enters them erroneously. Moreover, MPMGW is useful in acute thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported the use of a modified pigtail-shaped MGW (MPMGW) for various endovascular treatments. [2][3][4][5][6] Although the MPMGW is effective for acute thrombectomy, the manual quick shaping of this wire requires some skills. The common measurement of the round tip is >3.0 mm.…”
Section: Introductionmentioning
confidence: 99%